Accuracy of ESR dating of small gastropods from loess and fluvial deposits in the Bavarian Alpine Foreland. (10th August 2020) - Schellmann, Gerhard; Schielein, Patrick; Burow, Christoph; Radtke, Ulrich
Abstract: This study focuses on the accuracy of the Electron Spin Resonance (ESR) dating method applied to small land snail shells from eolian loess deposits, and from shell bearing clods of sandy loam and marl in fluvial gravel deposits in the Bavarian Alpine Foreland. Due to the small size of land snail shells and lack of specimens available for ESR analysis it was necessary to reduce individual aliquot sample weights to 0.02–0.07 g. While the reduction in sample weight inevitably lowers the signal-to-noise ratio and thus may also negatively influence the precision on the equivalent dose due to even smallest weight variations between the single aliquots, the dating results are in good agreement with independent age control. In general, the ESR ages are mostly within the age interval of previous and new luminescence or radiocarbon dating results. We show that ESR dating of small terrestrial gastropods in most cases allows differentiating between shells of Holocene, Late or Middle Würmian (last glacial, MIS 3, 2), penultimate glacial (MIS 6) or penultimate interglacial (MIS 7) age with errors between c. 10%–15%.